German Experience In Improving The Efficiency Of Public Administration - Azizxon Ahmedov Muhsinjon o’g’li (Genius Journals, 2022)
This article discusses modern aspects of effective organization of public administration in the Federal Republic of Germany. Improving governance and effective governance have always been important in the world. In developed countries, we can see that due to the efficiency, effectiveness and transparency of public administration, budget funds are spent wisely, corruption is low, bureaucratic barriers are reduced, and the relationship between citizens and government agencies is systematic.
Keywords: Public administration; cardinal reforms; Management efficiency; outsourcing